Decitabine Induces Change of Biological Traits in Myelodysplastic Syndromes via FOXO1 Activation - Zhang, Zheng; Jia, Yan; Xv, Feng; Song, Lu-xi; Shi, Lei; Guo, Juan; Chang, Chun-kang (Frontiers in Genetics, 2021)
Decitabine (DAC) is considered to be a profound global DNA demethylation, which can induce the re-expression of silenced tumor suppressor genes. Little is known about the function of tumor suppressor gene FOXO1 in myelodysplastic syndromes (MDS). To address this issue, the study firstly investigated differentially expressed genes (DEGs) for DAC treatment in MDS cell lines, then explored the role of FOXO1 by silencing its expression prior to DAC treatment in MDS. We found that FOXO1 exists in a hyperphosphorylated, inactive form in MDS-L cells. DAC treatment both induces FOXO1 expression and reactivates the protein through reducing its phosphorylation level. Furthermore, we showed that this FOXO1 activation is responsible for the DAC-induced apoptosis, cell cycle arrest, antigen differentiation, and immunoregulation in MDS-L cells. We also demonstrated DAC-induced FOXO1 activation upregulates anti-tumor immune response in higher-risk MDS specimens. Collectively, these results suggest that DAC induces FOXO1 activation, which plays an important role in anti-MDS tumors.